Effects of Antenatal Education Program on Postpartum Functional Status and Depression - CAN GÜRKAN, ÖZLEM; EKŞİ GÜLOĞLU, ZÜBEYDE (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Objective: The aim of the study was to determine the effects of antenatal education on the functional status and depression in women who were in the 6th postpartum week and in the 6th postpartum month. Methods: The nonrandomized, post-test-control group design was used. The study was conducted on pregnant women who applied to the prenatal center of a hospital in Istanbul. The participants in the education group attended the antenatal education program, whereas those in the control group received routine antenatal care. The study was completed with 65 participants (education group=31 and control group=34). Data collection was performed using the Demographic Questionnaire, the 6th Week Assessment Form, the Inventory of Functional Status after Childbirth (IFSAC), and the Edinburgh Postpartum Depression Scale (EPDS). Results: The results showed that there was no significant difference in terms of both the EPDS scores and IFSAC scores between the groups at both the 6th week and the 6th month (p>0.05). Conclusion: It was found that antenatal training may not be effective in decreasing postpartum depression and in improving the postpartum functional status.
Keywords: Antenatal education; postpartum depression; postpartum functional status; nursing; POSTNATAL DEPRESSION; PRENATAL EDUCATION; MOTHERS; WOMEN